KOMUNIKASI KESEHATAN - Rifqi Fauzi; Mia Nur Islamiah (INSTITUT AGAMA ISLAM NEGERI METRO, 2022)
Communication is a stimulating process in the form of a symbol and a verbal and non-verbal language, to influence the behavior of others. Health communication is a part of human communication with the main focus on how individuals deal with health issues and how they attempt to maintain their health. Health communication utilizes communication services to positively influence the health behavior of individuals, families and communities. Health communication includes information on disease prevention, health promotion, and health care policy and to increase individual awareness about health issues, health problems, health risks and health solutions. Media advocacy, media, entertainment and internet media are various forms of health communication with the aim to improve and maintain health.